Establishment of a 3D Co-culture With MDA-MB-231 Breast Cancer Cell Line and Patient-Derived Immune Cells for Application in the Development of Immunotherapies - Saraiva, Diana P. (2020)
Funding: This work was supported by Tagus Tank Consortium Projects in Medicine Award; Terry Fox 2019 Research Grant from Liga Portuguesa Contra o Cancro; Fundação para a Ciência e Tecnologia (PD/BD/114023/2015 and PD/BD/114053/2015) and iNOVA4Health (UIDB/04462/2020 and DAI/2019/46).